Adatom Defect Induced Spin Polarization of Asymmetric Structures. Issue 2 (1st February 2022) - Wang, Jia; Liu, Xuhui; Wang, Chunxu; Zhang, Wanyi; Qin, Zhengkun
Abstract: The spin polarization of carbon nanomaterials is crucial to design spintronic devices. In this paper, the first‐principles is used to study the electronic properties of two defect asymmetric structures, Cap‐(9,  0)‐Def [6,  6] and Cap‐(9,  0)‐Def [5,  6]. We found that the ground state of Cap‐(9,  0)‐Def [6,  6] is sextet and the ground state of Cap‐(9,  0)‐Def [5,  6] is quartet, and the former has a lower energy. In addition, compared with Cap‐(9,  0) CNTs, the C adatom on C30 causes spin polarization phenomenon and Cap‐(9,  0)‐Def [6,  6] has more spin electrons than Cap‐(9,  0)‐Def [5,  6] structure. Moreover, different adsorb defects reveal different electron accumulation. This finding shows that spin polarization of the asymmetric structure can be adjusted by introducing adatom defects. Abstract : Two defect asymmetric structures Cap‐(9,  0)‐Def [6,  6] CNT and Cap‐(9,  0)‐Def [5,  6] CNT have been constructed, and the former has a lower energy. In addition, the C adatoms on C30 causes spin polarization phenomenon, and Cap‐(9,  0)‐Def [6,  6] CNT has more spin electrons than Cap‐(9,  0)‐Def [5,  6] CNT.